In-vivo and in-vitro toxicity evaluation of 2,3-dimethylquinoxaline: An antimicrobial found in a traditional herbal medicine - Alfadil, Abdelbagi; Alsamhan, Hamoud; Ali, Ahmed; Alkreathy, Huda; Alrabia, Mohammad W.; Fatani, Asif; A. Ibrahem, Karem (PLOS ONE, 2024)
2,3-dimethylquinoxaline (DMQ) is a broad-spectrum antimicrobial phytochemical. This study aims to assess its toxicological profile. In vitro studies conducted in appropriate cell cultures, included assessment of cardiotoxicity, nephrotoxicity, and hepatotoxicity. An in vivo study was conducted in mice to determine acute oral toxicity (AOT), and subacute oral toxicity (SAOT). Acute dermal toxicity (ADT) was conducted in rats. All in-vitro toxicity studies of DMQ had negative results at concentrations ≤100 μM except for a non-significant reduction in the ATP in human hepatocellular carcinoma cell culture. The median lethal dose of DMQ was higher than 2000 mg/kg. All animals survived the scheduled necropsy and none showed any alteration in clinical signs. Biochemistry analysis revealed a significant difference between the satellite and control groups, showing an increase in platelet counts and white blood cell counts by 99.8% and 188.8%, respectively. Histology revealed enlargement of renal corpuscles; hyperplasia of testosterone-secreting cells; and dilatation of coronaries and capillaries. The present data suggests an acceptable safety profile of DMQ in rodents except for thrombocytosis, leukocytosis, and histological changes in high doses that need further investigation.